2016
DOI: 10.1038/mp.2016.113
|View full text |Cite
|
Sign up to set email alerts
|

Clinical genomics expands the morbid genome of intellectual disability and offers a high diagnostic yield

Abstract: Intellectual disability (ID) is a measurable phenotypic consequence of genetic and environmental factors. In this study, we prospectively assessed the diagnostic yield of genomic tools (molecular karyotyping, multi-gene panel and exome sequencing) in a cohort of 337 ID subjects as a first-tier test and compared it with a standard clinical evaluation performed in parallel. Standard clinical evaluation suggested a diagnosis in 16% of cases (54/337) but only 70% of these (38/54) were subsequently confirmed. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
188
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(210 citation statements)
references
References 46 publications
12
188
0
3
Order By: Relevance
“…We have previously shown that the mutation spectrum of genetically heterogeneous diseases is dominated by autosomal recessive mutations in our highly inbred populations (Patel et al 2015; Anazi et al 2016; Alazami et al 2016). We show in this study that cataract displays a similar trend with recessive mutations accounting for 87% of all identified mutations.…”
Section: Discussionmentioning
confidence: 94%
“…We have previously shown that the mutation spectrum of genetically heterogeneous diseases is dominated by autosomal recessive mutations in our highly inbred populations (Patel et al 2015; Anazi et al 2016; Alazami et al 2016). We show in this study that cataract displays a similar trend with recessive mutations accounting for 87% of all identified mutations.…”
Section: Discussionmentioning
confidence: 94%
“…There is no reported case of a deletion only in the FEZF2 gene with ID and/ or other phenotypic features that could support its importance in pathogenicity. However, the importance of FEZF2 for ID and developmental delay is shown in a recently described patient with a homozygous point mutation in the gene presenting with brain atrophy, suspected Dandy-Walker malformation, and microcephaly detected by cerebral MRI [Anazi et al, 2017]. Finally, the PTPRG tumor suppressor gene, which is outside of the suggested critical region [de la Hoz et al, 2015] and does 180 not seem to be relevant in the determination of ID and dysmorphisms (with a few exceptions) [Kranz et al, 2016], is also partially involved in our deletion.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that Arg176 and Ala210 are critical for the glucose transport activity of SLC45A1. Anazi et al 10 recently reported a homozygous c.167T>C (p.Ile56Thr) missense mutation in SLC45A1 (or c.269T>C [p.Ile90Thr]; GenBank: NM_001080397.2) in a 5-year-old girl with developmental delay, ataxia, and Dandy-Walker malformation. Although this phenotype somewhat overlaps that of our affected individuals, none of our individuals had cerebellar abnormalities.…”
mentioning
confidence: 99%